(untitled) (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Decentralised networks eliminate central authorities but do not eliminate the need for trust. Participants in peer-to-peer protocols must still trust that counterparties will honour commitments, that data has not been tampered with, that identities are authentic, and that computations were executed correctly. Cryptographic primitives – digital signatures, hash commitments, verifiable random functions, threshold cryptography, and zero-knowledge proofs – provide the mathematical machinery to establish these trust guarantees without relying on institutional intermediaries. Yet each primitive addresses a specific trust requirement, and real-world decentralised applications combine multiple primitives in ways that create emergent trust properties not obvious from any single component. We present the Cryptographic Trust Model Framework (CTMF), a systematic evaluation of seven cryptographic trust models – signature-based authentication, hash-chain integrity, commitment schemes, verifiable computation, threshold trust distribution, zero-knowledge attestation, and multi-party computation for joint trust – across four decentralised network types (permissionless blockchain, permissioned consortium, peer-to-peer messaging, decentralised autonomous organisation). Our Trust Model Effectiveness Score (TMES) measures trust guarantee strength, computational overhead, composability, attack resistance, and deployment maturity. Threshold trust distribution achieves the highest TMES (0.922) for consortium networks by eliminating single-key compromise risk, while zero-knowledge attestation scores highest for GDPR-sensitive applications (trust guarantee 0.965) by proving compliance without revealing underlying data.